2021
DOI: 10.3233/efi-200442
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the journal impact factor and related bibliometric indicators in education and educational research category

Abstract: This study analyzes the journal impact factor and related bibliometric indicators in Education and Educational Research (E&ER) category, highlighting the main differences among journal quartiles, using Web of Science (Social Sciences Citation Index, SSCI) as the data source. High impact journals (Q1) publish only slightly more papers than expected, which is different to other areas. The papers published in Q1 journal have greater average citations and lower uncitedness rates compared to other quartiles, al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 61 publications
1
8
0
2
Order By: Relevance
“…As a result, the average number of citations per paper increased over time as a natural consequence of increased international collaboration in educational research (Althouse et al, 2009). Orbay et al (2021) studied the international collaborations in the top 10 most productive countries in the education research in the period from 2013 to 2018 and established that international collaboration increased to higher levels as compared to the values established in Aman and Botte's (2017) study; namely, from 20.6% in 2013 to 29.1% in 2018. On the other hand, a study conducted in the field of special education by O ¨rnek et al ( 2021) pointed out that the international collaboration rate was almost constant in the period from 2014 to 2018 and that the rate of international collaboration for the 10 most productive countries was 36.96% in 2014, 38.06% in 2015, 38.82% in 2016, 33.77% in 2017, and 36.61% in 2018 (average 36.56% in the period of [2014][2015][2016][2017][2018].…”
Section: Findings and Discussion For Rq1mentioning
confidence: 99%
“…As a result, the average number of citations per paper increased over time as a natural consequence of increased international collaboration in educational research (Althouse et al, 2009). Orbay et al (2021) studied the international collaborations in the top 10 most productive countries in the education research in the period from 2013 to 2018 and established that international collaboration increased to higher levels as compared to the values established in Aman and Botte's (2017) study; namely, from 20.6% in 2013 to 29.1% in 2018. On the other hand, a study conducted in the field of special education by O ¨rnek et al ( 2021) pointed out that the international collaboration rate was almost constant in the period from 2014 to 2018 and that the rate of international collaboration for the 10 most productive countries was 36.96% in 2014, 38.06% in 2015, 38.82% in 2016, 33.77% in 2017, and 36.61% in 2018 (average 36.56% in the period of [2014][2015][2016][2017][2018].…”
Section: Findings and Discussion For Rq1mentioning
confidence: 99%
“…On the other hand, it is possible to see similar results in studies focused on citation skewness, especially educational journals and special education journals indexed in the WoS database between 2014 and 2018 (Orbay, Karamustafaoğlu, & Miranda, 2021;Örnek, Miranda, & Orbay, 2021).…”
Section: Findings and Discussion For Rq2mentioning
confidence: 55%
“…Similarly, in a study of educational research by the twenty most prolific European countries between 2002 and 2013, Aman and Botte (2017) revealed that the number of articles produced by international cooperation in education increased steadily from 14.1% in 2002 to 21.7% in 2013. In a similar study, Orbay et al (2021) showed that internationalization increased from 20.6% in 2013 to 29.1% in 2018.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…TÜBİTAK Türkiye Adresli Uluslararası Bilimsel Yayınları Teşvik (UBYT) Programı çerçevesinde desteklenen makalelerin ortalama atıf sayısı destek almayanlara oranla biraz daha yüksektir (Tonta ve Akbulut, 2020, s. 1627. Dergi etki faktörü yüksek Q1 dergilerinde yayımlanan TR adresli makalelerin ortalama atıf sayısı daha yüksek, bu dergilerde yayımlanan ve hiç atıf almayan makalelerin oranı ise daha düşüktür (Orbay, Karamustafaoğlu ve Miranda, 2021;Orbay, Miranda ve Orbay, 2020). Ancak dünyada makalelerin yaklaşık %40'ı Q1 dergilerinde yayımlanırken, TR adresli makalelerde bu oran sadece %21'dir (Tonta ve Akbulut, 2020, s. 1627.…”
Section: Literatür Değerlendirmesiunclassified